Electrophysiological effects of anthracyclines in adult survivors of pediatric malignancy. Issue 11 (28th April 2017) - Markman, Timothy M.; Ruble, Kathryn; Loeb, David; Chen, Allen; Zhang, Yiyi; Beasley, Gary S.; Thompson, W. Reid; Nazarian, Saman
Abstract: Background: Anthracycline use is limited by cardiotoxicity, including arrhythmias and left ventricular (LV) dysfunction. We aim to characterize the association between electrophysiological changes and LV dysfunction. Methods: A retrospective chart review was conducted, including all 147 pediatric cancer survivors at our institution over 18 years of age and treated with an anthracycline. One hundred thirty‐four patients who had at least one electrocardiogram (ECG) and echocardiogram were analyzed. The association between dysfunction and baseline characteristics, treatment history, and electrocardigraphic parameters were analyzed using multivariable logistic regression. Additionally, a longitudinal generalized estimating equation (GEE) model was used to examine the temporal association between repeated measure corrected QT (QTc) intervals and subsequent LV function. Results: In our population, 24% of patients had LV dysfunction. The initial posttreatment QTc interval was longer in patients with LV dysfunction (438 ± 35 vs. 420 ± 20 msec, P = 0.002). In logistic regression analysis, QTc interval ( P < 0.001) and cumulative radiation dose ( P = 0.027) were associated with LV dysfunction. On ECGs performed prior to evidence of LV dysfunction, the QTc was longer than on ECGs preceding a normal echocardiogram (451 ± 32 msec vs. 423 ± 25 msec, P < 0.001). Mean time from QTc ≥ 450 msec to evidence of LV dysfunction was 1.8 ± 2.9 years. In the longitudinal GEE model, QTc prolongation was associated with subsequent decreased fractional shortening. Conclusions: Among adult survivors of pediatric cancer treated with anthracyclines, prolongation of the QTc interval was associated with subsequent LV dysfunction.